Liver involvement associated with dengue infection in adults in Vietnam. - Trung, D; Thao, L; Hien, T; Hung, N; Vinh, N; Hien, P; Chinh, N; Simmons, C; Wills, B (2010)
Globally, the number of adults hospitalized with dengue has increased markedly in recent years. It has been suggested that hepatic dysfunction is more significant in this group than among children. We describe the spectrum and evolution of disease manifestations among 644 adults with dengue who were prospectively recruited on admission to a major infectious disease hospital in southern Vietnam and compare them with a group of patients with similar illnesses not caused by dengue. Transaminase levels increased in virtually all dengue patients and correlated with other markers of disease severity. However, peak enzyme values usually occurred later than other complications. Clinically severe liver involvement was infrequent and idiosyncratic, but usually resulted in severe bleeding. Chronic co-infection with hepatitis B was associated with modestly but significantly increased levels of alanine aminotransferase, but did not otherwise impact the clinical picture.